Visioneer paperPort software User's guide for windows (West Bayshore, 1995)
Content: scaning items;working on the paperPort desktop; woking with stacks; getting items on and off the paperPort desktop; annotating items; using paperPort links.
Keywords: Computer systems,Hệ thống máy tính,Computer software,Phần mềm máy tính